2022
DOI: 10.3390/ijerph19138013
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Factors Influencing the Severity of the Symptoms of Long COVID

Abstract: COVID-19 is a highly contagious respiratory disease. Infection with the virus can occur with differing symptom severity, from mild and moderate to severe cases, but the long-term consequences of infection have not been fully identified or studied. Long COVID is defined as occurring in individuals with a history of probable or confirmed SARS-CoV-2 infection, and symptoms persisting for at least two months within three months of onset that cannot be explained by an alternative diagnosis. The purpose of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 62 publications
(73 reference statements)
3
11
0
Order By: Relevance
“…3 Therefore, a reliable and appropriate test is needed to predict the severity of COVID-19 disease. 2 Recently, several studies have reported that C-reactive protein (CRP) is directly associated with the severity of infection, and patients with higher CRP in the early stages of the disease are at greater risk for severe disease. 5 CRP, first described by Tillet and Francis, is released from the liver in response to interleukin-6 (IL-6) and it is an inflammatory test that is available everywhere.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Therefore, a reliable and appropriate test is needed to predict the severity of COVID-19 disease. 2 Recently, several studies have reported that C-reactive protein (CRP) is directly associated with the severity of infection, and patients with higher CRP in the early stages of the disease are at greater risk for severe disease. 5 CRP, first described by Tillet and Francis, is released from the liver in response to interleukin-6 (IL-6) and it is an inflammatory test that is available everywhere.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis for patients is not fully understood, and the type and severity of the consequences of COVID-19 may depend, inter alia, on the severity of the course of the infection, age, and comorbidities. 2 Extreme COVID-19 is characterized by interleukin waves, organ dysfunction disease, and destruction of many metabolic processes, including coagulation factors and blood clotting. 3 Therefore, a reliable and appropriate test is needed to predict the severity of COVID-19 disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The model can accurately reflect the spread and outbreak. The model is an infectious disease model with an incubation period [ 14 ]. It is designed to calculate the changes in the target population that needs to be screened.…”
Section: Epidemiological Model Proposalmentioning
confidence: 99%